Molecular structure of the ESCRT-III-based archaeal CdvAB cell division machinery - Tina Drobnič; Ralf Salzer; Tim Nierhaus; Margaret Ke Xin Jiang; Dom Bellini; Astrid Steindorf; Sonja-Verena Albers; Buzz Baum; Jan Löwe (Proceedings of the National Academy of Sciences, 2026)
Most prokaryotes divide using filaments of the tubulin-like FtsZ protein, while some archaea employ instead ESCRT-III-like proteins and their filaments for cell division and cytokinesis. The alternative archaeal system comprises Cdv proteins and is thought to bear some resemblance to ESCRT-III-based membrane remodeling in other domains of life, including eukaryotes, especially during abscission. Here, we present biochemical, crystallographic, and cryo-EM studies of the Sulfolobus Cdv machinery. CdvA, an early non-ESCRT component, adopts a PRC‐domain/coiled-coil fold and polymerizes into long double-stranded helical filaments, mainly via hydrophobic interfaces. Monomeric CdvB adopts the canonical ESCRT-III fold in both a closed and a distinct “semiopen” conformation. Soluble CdvB2 filaments are composed of subunits in the closed state, appearing to transition to the open, active state only when polymerized on membranes. Short N-terminal amphipathic helices in all CdvB paralogues, B, B1, and B2, mediate membrane binding and are required for liposome recruitment in vitro. We provide a molecular overview of archaeal ESCRT-III-based cytokinesis machinery, the definitive demonstration that CdvB proteins are bona fide ESCRT-III homologues, and reveal the molecular basis for membrane engagement. Thus, we illuminate conserved principles of ESCRT-mediated membrane remodeling and extend them to an anciently diverged archaeal lineage.